EVALUASI PELAKSANAAN PROGRAM KEMITRAAN DI AREA MEDAN OLEH PT. PERKEBUNAN NUSANTARA SUMATERA UTARA - ANNA ALFI YANTI HULU (Welfare StatE, 2012)
There are various cases about the relationship between a company and community in some countries nowdays. Some companies take only the available natural resources in one region and ignore the environment as well as its surrounding environment. Regarding the issue, the social responsibility of company had become a central issue in some countries including Indonesia. In solving the problem, the government of Indonesia tries to create the rule regarding the social responsibility of the company. This rule obliges the company to implement its social responsibility. PT. Perkebunan Nusantara IV is one of the companies which performs its social responsibility through a partnership program. This program is intended to support community small bussinesses. Related to this program, I carried out the research about the implementation of partnership program by PT. Perkebunan Nusantara IV in Medan area. The results of the research indicated that the implementation of partnership program by PT. Perkebunan Nusantara IV had been in accordance with its expectation to increase partnership business. Partnership Program is able to expand employment and improve the living standards of the people towards prosperity.